Investigation of new education methods using applied mechatronics - (:unkn) unknown (Nova Science Publishers, Inc., 2010)
Mechatronics is an area that merges multidisciplinary knowledge coming from mechanical engineering, electronics and computer technology. Vocational training in mechatronics requires the teaching of "multi-skills" and "multi-intelligent" in various learning contexts, as well as a good blend of learning in the classroom and practical training in schools where is steered with quality management system. Quality education is the education in which the provider offers education services in accordance with certain standards, develops skills, attitudes that enable a person to accede to a higher stage of career development, self discovery, personality development, adaptability to labor market and life long learning. Quality in education must be defined not only on the basis of what is needed now for an adult or a young person but depending on how it manages to meet future needs. A quality education is not only to ensure progress in achieving predetermined objectives, but also to set new trends and new ways of achieving them. Vocational training colleges together with industry are confronted with the need to develop and integrate theoretical and practical learning sequences that are able to fulfill the demands for multi-skilled technicians and skilled workers. The claim for work-related learning based on the interleaving of theoretical learning and learning by practical work and experimentation is obvious [1] A major goal in mechatronics training is that students have to acquire theoretical and operational knowledge and practical competencies in terms of technical core skills. This type of skills generally relates to the assembly and service of complex machines, plants and systems, in the field of plant construction and mechanical engineering, and in those companies that purchase and operate such mechatronic systems. It describes the effect of some learning methods that apply quality management in an organized educational environment and system. Mechatronics is an interdisciplinary science, so we have to use different learning methods according to the curricula's specific target. The main aim of this paper is to increase the learning levels of mechatronics education in order to have and efficient assessment [2]. © 2011 Nova Science Publishers, Inc. All rights reserved.